Renewable-Powered Seawater Desalination: Technologies, Challenges, and Opportunities with a Focus on Morocco - Riffi Temsamani Yasmina; Al Mers Ahmed; Filali Baba Yousra (EPJ Web of Conferences)
Water scarcity is one of the most pressing global challenges, intensifying with the growing demand for freshwater and the impacts of climate change. Seawater desalination has emerged as a viable solution to address this issue, offering a reliable alternative to traditional water sources. This review comprehensively overviews current desalination technologies, including thermal processes, membrane-based, and emerging hybrid methods. It also explores the integration of renewable energy sources into desalination systems to mitigate their environmental impact, reduce energy consumption, and enhance economic feasibility. Special attention is given to Morocco, a country actively implementing renewable-powered desalination projects to address its severe water scarcity, while also aligning with its ambitious renewable energy and sustainability goals. By examining Morocco’s initiatives, this review identifies the opportunities, technical barriers, and policy challenges associated with scaling up renewable-powered desalination in other water-stressed regions. However, despite its potential, desalination poses significant environmental concerns, particularly the disposal of concentrated brine into marine ecosystems, which can harm biodiversity and water quality. This review concludes by analyzing ecological challenges and proposing innovative strategies to mitigate the harmful effects of brine discharge.